Memoir of Kidung Rumekso Ing Wengi in the Frame of Symbolism - Danur Putut Permadi (Islah: Journal of Islamic Literature and History, 2022)
Da'wah method in teaching Islamic values can at least occur using two approaches, namely Islamization of Javanese culture and Jawanize Islam. The walisongo in carrying out his da'wah using the approach to the Jawanize Islam, no exception Sunan Kalijaga. In carrying out his da'wah duties, Sunan Kalijaga always uses local culture as a media da'wah. Many cultural-based works were triggered by Sunan Kalijaga, one of which was Kidung Rumekso Ing Wengi. This is a poem with the theme of the teachings of Islam using Javanese. Using a qualitative research method can be obtained by several conclusions. Some of the results of the study are that the song is a means of teaching to the community to always remember God. In addition, the song has two core da'wah messages. The first is to teach to be sure of God and secondly teaches to be able to establish a good relationship with each other. And the third result is that the appointment included in the song is the hope of being a figure in the song in accordance with the special thing on the character.